Reading Lists, learning support tools: Leganto - Diez-Diez, Ángela; Riesco-Peláez, Mª Aurora (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article describes the implementation method of the Leganto reading list management system through three subjects of the University of León (ULE). This has been a collaborative process between the library staff and the teaching staff, which has allowed us to analyze how to integrate this resource into the learning process of our students. This tool enhances and stimulates the use of library resources and facilitates the updating of part of the information in the teaching guides.